Factors Affecting Employee Commitment to Change in Malaysia Service Organizations : The Moderating Impact of Organization Culture - Lim, Sing Yee; Lo, May-Chiun; Mohamad, Abang Azlan; Suaidi, MOHAMAD KADIM; Ramayah, T. (Ascociacion Internacional de Economia Aplicada, 2021)
Organizational change has been receiving tremendous concern lately as the everchanging environment causes companies to succumb to changes. Employee commitment towards change is detrimental in an organizational change. This research aims to investigate the factors that affect employee commitment to change and to examine the moderating effect of organization culture in service organizations. A total of 190 responses was collected from the employees working in the service organizations in Malaysia. Smart PLS 3.0 was used for data analysis. The proposed research model was assessed based on path modeling and bootstrapping. The findings found that among the four factors, only quality of relationship with the manager, fit of change with vision, and job motivation are significantly related to employee commitment to change. Moreover, the results have found no empirical evidence to support the moderating role of organization culture. The implications, limitations and future research were further discussed in this research.